An extensive model for implementing competency‐based training in technical and vocational education and training teacher training system for Assiut‐Integrated Technical Education Cluster, Egypt. Issue 2 (5th April 2021) - Ahmed, Adel; Sayed, Khairy
Abstract: A Competency‐Based Training Program—Education Competency—is designed to provide professional adult training for international educators who wish to advance or acquire new professional skills. It is an intensive training program intended for capacity building for people with an education and training background. Once a training topic is nominated, Assiut‐Integrated Technical Education Cluster can source appropriate facilitators and design a suitable training solution to meet specified objectives and training modules. This program can be delivered in various formats, including workshops, seminars, school visits, case studies, coaching, and mentoring. One of the objectives of this advanced training is to know the German vocational training system and understand the related training‐oriented training concepts.